Al-Nusairat, Saleh M. “Fethullah Gulen: A Turkish Sufi in the Era of Globalization,” Year 9, Issue 36 (Spring 1425 AH/ 2004 CE), Pp. 159-178. - نصيرات, صالح محمد (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2004)
Saleh Al-Nusairat’s article offers a biographical sketch and an analysis of the thought of the Turkish scholar and preacher Fethullah Gulen. It discusses his character, the movement he established, the conditions and circumstances in which it developed, its basic principles, and the impact the movement had on Turkish society. The focal points of his article include the Sufi nature of his movement, relationship with others, international relations from an Islamic perspective, and tolerance and dialogue.